Duration Adaptation Occurs Across the Sub- and Supra-Second Systems - Shima, Shuhei; Murai, Yuki; Hashimoto, Yuki; Yotsumoto, Yuko (Frontiers in Psychology, 2016)
After repetitive exposure to a stimulus of relatively short duration, a subsequent stimulus of long duration is perceived as being even longer, and after repetitive exposure to a stimulus of relatively long duration, a subsequent stimulus of short duration is perceived as being even shorter. This phenomenon is called duration adaptation, and has been reported only for sub-second durations. We examined whether duration adaptation also occurs for supra-second durations (Experiment 1) and whether duration adaptation occurs across sub- and supra-second durations (Experiment 2). Duration adaptation occurred not only for sub-second durations, but also for supra-second durations and across sub- and supra-second durations. These results suggest that duration adaptation involves an interval-independent system or two functionally related systems that are associated with both the sub- and supra-second durations.